Alveolar Bone Grafting in Unilateral Cleft Lip and Palate: Impact of Timing on Palatal Shape - Brudnicki, Andrzej; Petrova, Tereza; Dubovska, Ivana; Kuijpers-Jagtman, Anne Marie; Ren, Yijin; Fudalej, Piotr S (Journal of clinical medicine, 2023)
Alveolar bone grafting (ABG) is a critical surgical intervention in patients with a cleft of the alveolus, aimed at reconstructing the alveolar ridge to facilitate proper eruption, periodontal support, and alignment of adjacent permanent teeth. The optimal timing for ABG remains debated, with late secondary ABG between the ages of 9 and 11 being widely adopted. This study compared the palatal shapes of 28 children at a mean age of 9.5 years (SD = 0.7) who underwent early secondary ABG at a mean age of 2.1 years (SD = 0.6) or 33 children at a mean age of 10.8 years (SD = 1.5) who underwent late secondary ABG at a mean age of 8.6 years (SD = 1.3) to 60 non-cleft controls at a mean age of 8.6 years (SD = 1.2). The palatal shapes were captured with 239 landmarks digitized on the palate on a digital model. Utilizing geometric morphometric methods, i.e., generalized Procrustes superimpositions, principal component analysis, and permutation tests, we assessed the impact of ABG timing on palatal morphology. The first five principal components (PCs) explained 64.1% of the total shape variability: PC1 = 26.1%; PC2 = 12%; PC3 = 11.9%; PC4 = 7.8%; and PC5 = 6.4%. The Procrustes distance between both cleft groups and the control group was more than twice as large as the Procrustes distance between the early ABG and late ABG groups. Nonetheless, all intergroup differences were statistically significant. Our findings suggest that early ABG has a limited negative effect on palatal shape, providing comparable outcomes to late ABG. The study highlights the potential suitability of early ABG, challenging conventional practices and encouraging further exploration into its long-term effects on maxillary growth.
Keywords: alveolar bone grafting; early secondary bone grafting; palatal shape; cleft palate